On Strike at Hormel The Struggle for a Democratic Labor Movement - Green, Hardy (Temple University Press, 2018)
In December of 1984, the members of United Food and Commercial Workers (UFCW) Local P-9 initiated a campaign against wage and benefit concessions at Geo. A. Hormel Company in Austin, Minnesota. By summer, they were involved in what many observers would come to regard as the strike of the decade, both because of the energy and imagination of the union members and because of the nationwide response to their cause. Nevertheless, by spring 1986, Hormel had proclaimed victory-and the strikers' unsympathetic International union brought an end to the strike by placing the local in receivership. The Austin strike was far from an ordinary labor dispute: For the 1,500 P-9 families and their supporters, it was nothing less than a crusade to defend the Middle American way of life. As a consultant for Corporate Campaign, Inc., a firm hired by the strikers to advance their cause, Hardy Green offers the first insider's account of this watershed strike. He traces the history of labor relations at Hormel and in the meatpacking industry, and outlines the innovative union techniques employed by the strikers, the "corporate campaign." Using records obtained through a comprehensive freedom-of-information project, Green reveals behind-the-scenes operations of the National Guard and various law enforcement agencies that proved crucial to breaking the strike. And he discusses the meaning of the local's dual fight-with both the Hormel company and with its own International union-within the current labor environment.